Experimental and simulation study of effect of thickness on performance of (butylene adipate-co-terephthalate) and poly lactide nanocomposites incorporated with graphene as stand-alone electromagnetic interference shielding and metal-backed microwave absorbers. (28th July 2020) - Kashi, Sima; Gupta, Rahul K.; Bhattacharya, Sati N.; Varley, Russell J.
Abstract: The dielectric properties induced by the presence of graphene nanoplatelets (GNP) in two polymeric matrices were measured experimentally and then used to predict their performances as both stand-alone shielding materials and metal-backed microwave absorbers. Periodic changes were observed in shielding effectiveness (SET ), with smaller periods for nanocomposites with higher GNP contents but the fluctuations dampened and higher SET was achieved as the sample thickness increased. Simulations were carried out to determine the required graphene content in each matrix and the optimum sample thickness to achieve 99% radiation attenuation over the entire X-band frequency range. Polylactide (PLA) nanocomposites with 9–15 wt% GNPs outperformed their corresponding poly(butylene adipate-co-terephthalate) (PBAT) nanocomposites. This was investigated by analysing the contributions of the dielectric constant and dielectric loss to radiation attenuation and was found to be due to the relatively segregated dispersion quality of graphene in PLA as a result of weaker interfacial interactions. The nanocomposites performances as microwave absorbers were also studied with the highest absorption belonging to PLA at 6 wt% GNPs, achieving a reflection loss of −49.87 dB. In contrast, PLA with 12 wt% GNPs exhibited wider effective absorption bandwidths of 1.53 GHz and 450 MHz with 90% and 99% radiation absorptions, respectively. The produced graphene nanocomposites proved to be effective both as stand-alone and metal-backed microwave absorbers; while higher GNP contents provided better EMI shielding for stand-alone nanocomposites, moderate GNP loadings performed exceptionally in metal-backed absorbers. Graphical abstract: Image 1